An experimental study of the integration of paper collage techniques and painting for primary school children / Noor Azura Baharudin - Baharudin, Noor Azura (2013)
This research is an Art-Based research conducted using experimental based study on media and materials that are suitable for the integration of paper collage techniques and painting for the use of primary school children. Paper is a material that is easy to use, have varieties of texture, types, colours and cheap in cost. In current syllabus, these two areas are taught separately. Suggestions of artwork were introduced by the researcher that hopes it will be given chances to be applied in school. Researcher had done experiments on standard four children and has come out with four suitable collage techniques using five types of paper. These collage techniques are combined with four types of painting media. Apart from that, researcher also done own experiment in studio to find the best approach to integrate collage techniques and painting. The workflow includes the preparation of materials for collage and the techniques to be used, the integration with painting using chosen media and the production of artwork as planned. The process to do this kind of artwork is suitable with the time period given in school. The finding of this study of the integration of paper collage techniques together with painting in a single artwork would be a new exploration for primary school children in their art activities.